The European Union banana market: demand estimation and evaluation of the new import regime - Chacón Cascante, Adriana (Kansas State University, 2006)
The EU is one of the world’s biggest importers of bananas and, as such, import policies enforced by this trade union are likely to have a great impact on major producers of bananas. Aiming to protect communitarian producers and exporters from selected ex-colonies of Africa, the Caribbean and Pacific and to honor previous agreements, the EU unified its import policy for bananas in 1993. This policy, known as the Common Market Organization for Bananas, generated one of the most controversial trade disputes in history. After several modifications of the original regime, in January 2006, the EU changed its import regime to satisfy a World Trade Organization mandate and to honor an agreement signed with the United States in 2000. This dissertation reviews the history of the trade disputes in the EU banana market and analyzes the effects that the new import regime will have on major suppliers. To do this, a theoretically-consistent demand system is estimated and then the calculated parameters are used to model the effects of the tariff-only import system in the EU banana market. Based on the results, producers surplus are estimated and Monte Carlo simulations are performed to do a sensitivity analysis of the results. In the demand estimation component, the EU market is modeled as a system containing four major suppliers using the Almost Ideal Demand System (AIDS). This estimation fills an important gap in literature regarding the lack of well-estimated demand elasticities of bananas in the EU. The EU banana market is then modeled based on a equilibrium displacement model framework. Results of this analysis are then used to calculate point estimates of producer surplus changes as a measure of the impact of the new import policy on banana suppliers. Monte Carlo simulations are based on parameter estimates obtained from the AIDS model. These simulations allowed not only sensitivity analysis but also probabilistic inferences about the statistical significance of the estimates obtained in the previous components. Results indicate that the hypothesis that the new import regime will not affect the major suppliers of the EU banana market cannot be rejected. This might indicate that the policy enforced by the Common Market Organization for Bananas and the current tariff-only import regime are statistically equivalent. In other words, the EU expertly enacted a tariff level that will leave much as status quo.
Keywords: European Banana market; Banana war; Tariffs; Quotas; WTO; Economics, Agricultural (0503)